Maturation Fetus Ascending Aorta Elastic Properties: Circumferential Strain and Longitudinal Strain by Velocity Vector Imaging - Zhong, Xin; Luo, Yuanchen; Zhou, Dan; Liu, Minghui; Zhou, Jiawei; Xu, Ran; Zeng, Shi (Frontiers in Cardiovascular Medicine, 2022)
Objective: To assess the circumferential and longitudinal strain of the fetal ascending aortic (AA) wall and establish a gestational age-associated longitudinal reference for aortic wall strain during the second half of pregnancy. Methods: Singleton fetuses with gestational age (GA) at 20+0 to 24+6 weeks were prospectively collected from a low-risk population. Global circumferential strain (GCS) and mean longitudinal strain (MLS) of the ascending aorta were measured serially at 4-week intervals using the vector velocity imaging (VVI) technique. Fractional polynomials were conducted to obtain the best-fitting curves between GA and AA strains. GA-specific reference percentiles of GCS and MLS were established by multilevel modeling. Results: A total of 223 fetuses with a total of 1127 serial observations were enrolled. GCS presented a second-degree fractional polynomial smoothing regression along GA (R2=0.635, P<0.05). Fetal aortic GCS remained unchanged at approximately 27.29% (20.36-35.60%) before 31 weeks and increased significantly from 31.36% (26.38-37.12%) at 31 weeks to 43.29% (30.50-56.78%) at term. MLS presented a third-degree fractional polynomial smoothing regression along GA (R2=0.465, P<0.05). MLS remained steady at approximately 10.03% (3.28-17.62%) between 20 and 31 weeks and then increased significantly from 12.68% (7.42-20.1%) at 32 weeks to 17.5% (9.67-25.34%) at term. The GCS was significantly higher than the MLS in the ascending aorta wall (p<0.001). Conclusion: The fetal ascending aorta wall demonstrates obviously greater circumferential strain than longitudinal strain. Both strains remained steady before the late trimester and then gradually increased until delivery, suggesting progressive maturation of aortic elasticity mechanics.